Nutrient and Water Acquisition Strategies of Oil Palm Fine Roots Enriched with Crops Species - Tonra, Melda Syam; Sulistijorini, Sulistijorini; Samhita, Sasya; Triadiati, Triadiati (Bogor Agricultural University, Indonesia, 2025)
Fine roots (≤2 mm diameter) are a plant organ that plays a major role in nutrient and water acquisition from the soil and a parameter for understanding belowground changes. Fine root traits can determine the plant's strategies in maximizing resource acquisition for productivity with an acquisitive strategy or maximizing resource investment with a conservative strategy. In this study, enrichment planting was carried out in oil palm plantations through a combination of oil palm and tree crops. It is necessary to determine whether enrichment planting can impact the nutrient and water acquisition of oil palm fine roots. Therefore, this study aimed to determine the nutrient and water acquisition strategies of oil palm fine roots enriched with crop species by analyzing differences in morphological traits through fine root inventory. The enrichment planting treatments were R0 (plot of oil palm without enrichment crop), R1 (plot of oil palm with one crop), R2 (plot of oil palm with two crops), R3 (plot of oil palm with three crops), and R6 (plot of oil palm with six crops/multispecies). The results showed that enrichment planting in oil palm plantations can be practiced with two and three crop species, as in plots R2 and R3, which support a conservative strategy with high RTD (root tissue density) and low SRL (specific root length) and SRA (specific root area) in oil palm fine roots. In contrast, high species diversity in plot R6 triggered a shift to an acquisitive strategy with high SRL and SRA and low RTD.